Analysis of the Construction Tender Process at the Bina Marga Public Works Office and the Goods/Services Procurement Unit of Sidoarjo District Using the Electronic Procurement Platform and the SWOT Method - Lesmana, Denny Indra; Witjaksana, Budi; Purnama, Jaka (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
The procurement of goods and services by the Government is essential for enhancing development, optimizing public services, and boosting economic growth in Indonesia, with significant expenditures reflected in the General Procurement Plan (RUP) amounting to Rp1,226.7 trillion nationally and Rp2,205 trillion in 2023. In this context, construction service providers are vital for implementing construction projects, which encompass planning, execution, and supervision across various disciplines. The electronic procurement service (LPSE) platform is one of the key platforms in the procurement process, ensuring transparency, accountability, and competition, while also identifying barriers faced by new suppliers, thereby suggesting areas for improvement in usability and accessibility. This study focuses on the implementation of road work package construction tenders in the Sidoarjo Regency area using the LPSE platform, covering the selection preparation, bid evaluation, winner determination, and work implementation processes, along with any problems encountered at each stage. The study also underscores the platform's suitability for large-scale construction project packages, reinforcing its strategic application in high-stakes environments, and utilizes up-to-date data from the 2023 and 2024 budget years.